ESOPHAGEAL CARCINOMA AND BLOOD GROUP AFFILIATION: ESOPHAGEAL CARCINOMA AND BLOOD GROUP AFFILIATION - Todorov, Velislav; Boycheva, Maria; Georgiev, Volodia; Minkov, Cvetan; Boichev, Milen; Georgieva, Rada (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The article describes a study of 92 patients (79 male and 13 female) with esophageal carcinoma - Ca oesophagii. The patients' blood type affiliation to AB0 and Rhesus factor systems was established. In comparison with the control group, consisting of healthy representatives of modern Bulgarian population, there was a statistically significant increase of disease incidence in patients with blood type A (by 22,60% to 66,30%) - P <0.05. In patients with other blood types there was a varying decrease of incidence (more pronounced in groups 0 and B). Significant sex-based dimorphism was observed in the distribution of the disease in the studied sample (predominantly male patients). We assume that blood type A affiliation is one of the risk factors for the development of this disease. In the Rhesus Factor system there were no differences between the studied sample and the control group.